1982
DOI: 10.1246/bcsj.55.2788
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Liquid Water by Neutron Scattering. II. Temperature Dependence of the Liquid Structure

Abstract: The structure factors for heavy water at 25, 50, 70, and 95 °C were determined in the range of Q, 1.4–20 Å−1, by means of the time-of-flight (TOF) neutron diffraction method using the electron linear accelerator (LINAC). An analysis of the neutron diffraction data was made by applying a new general theoretical procedure of analysis for the fluid system composed of molecular clusters with various sizes. Structure factors were calculated according to the general procedure for the pentamer-monomer mixture model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This trend continues as the liquid enters the supercooled region as shown in figure 2 which also includes new data from Ohtomo et al [7]. The differential displacement becomes greater as the temperature falls and, it is interesting to note that the diffraction peak for amorphous D20 ice occurs at 1-70 A -1 [4].…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This trend continues as the liquid enters the supercooled region as shown in figure 2 which also includes new data from Ohtomo et al [7]. The differential displacement becomes greater as the temperature falls and, it is interesting to note that the diffraction peak for amorphous D20 ice occurs at 1-70 A -1 [4].…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 73%
“…The variation in the position of the main diffraction peak for neutron scattering by liquid D20 at various temperatures ; +, present results (A=0.7 A) ; A, Walford and Dore[4] (1.13 A) ; ~, Gibson and Dote[4] (0.5, 1-07 A) ; x , Ohtomo[7] (pulsed neutrons). The ADM(Q, T) function for liquid D20 using a reference temperature, To, of 21°C.…”
mentioning
confidence: 98%
“…Ohtomo et al proposed a tetrahedrally coordinated pentamer-monomer model to estimate the liquid structure of water. 37 They concluded that the molar ratio of the water monomer and pentamer at 368 K were 0.45 and 0.55, respectively. If the monomer ratio is 0.45 and there are only monomers and pentamers in the system, the concentration of the water monomer is estimated to be about 7000 mol/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is suggested that the monomer concentration of water is lower than 9800 mol/m 3 . Ohtomo et al proposed a tetrahedrally coordinated pentamer−monomer model to estimate the liquid structure of water . They concluded that the molar ratio of the water monomer and pentamer at 368 K were 0.45 and 0.55, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The main improvement in the design of our freezing device is the ability to irradiate the biological specimen with microwaves at 2.45 GHz for a short period of time (about 50 ms) during cryoquenching. Microwaves at 2.45 GHz are specifically absorbed to break the pentamer microclusters of water molecules, which are estimated to occupy 85% of total water at 298 K (Ohtomo et al, 1982), as drawn schematically in Fig. 1 .…”
Section: Design For the Freezing Devicementioning
confidence: 99%